Frequency and carbapenems susceptibility profile of non-fermenting Gram-negative bacilli isolated from clinical samples between 2007 and 2012 - Milena Cristina de Paula; Rachel M. Monteiro; Pedro C. A. Domingues; Paula Regina S. Hermann; Denise de Andrade; Adriano M. Ferreira; Evandro Watanabe (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: One of the major problems in health services is the occurrence of healthcare-associated infections (HAIs) by microorganisms resistant to various antimicrobials. Objectives: To describe the frequency and susceptibility profile of Pseudomonas aeruginosa and Acinetobacter baumannii to carbapenems in the hospital from Fundação Santa Casa de Franca, São Paulo, Brazil. Methods: The susceptibility of P. aeruginosa and A. baumannii to carbapenems from 304 clinical isolates between 2007 and 2012 was retrospectively analyzed from a microbiology database at the clinical laboratory of the hospital of Fundação Santa Casa de Franca, São Paulo, Brazil. Results: From isolated and identified strains, 236 (5.3%) P. aeruginosa were susceptible to imipenem (2007 - 69.6% to 2012 - 41.7%) and meropenem (2007 - 63.3% to 2012 - 25%). In addition, all 68 (1.7%) A. baumannii isolates were susceptible to both antibiotics. Conclusion: A. baumannii resistance to carbapenems was not identified; however, there was a decrease in susceptibility to carbapenems over the years for P. aeruginosa.